Cyberspace- advantages and its disadvantages - Bruce-Quaye, Philip (Univerzita Pardubice, 2016)
This study seeks to collect and describe advantages and disadvantages of the cyberspace and touching on the main threats in cyberspace as well as its threat in the global world. Also some areas such as cyber security, cyber bullying, cybercrime, information society and finally, cyber threats have also been talked about in this thesis.
Cyberspace- výhody a nevýhody
Keywords: cyberspace; cyber-attacks; cyber threat; cyber conflict; cybercrime; cyber security; cyber bullying; kyberprostor; kybernetické útoky; kybernetické hrozby; kybernetické konflikty; počítačová kriminalita; kybernetická bezpečnost; kyberšikana